THE IDENTIFICATION OF INCOME CONTINGENT TRANSACTION IN LOCAL GOVERNMENT ENTITIES - Yusram Yusram; Fransiskus Randa; Sherly E Tanamal (Magister Akuntansi, Universitas Atma Jaya Makassar, 2022)
This study is intended to identify contingent income transactions in local government entities. The research was conducted using qualitative methods through in-depth interviews and field observations. The key informants in this study were BPKAD staff in East Luwuk district. The results show that the local government revenue account indicated as a contingent transaction is due to a formal engagement through a contract or engagement. Recognition of revenue that is tied to the contact requires that new revenue be recognized if the engagement is fulfilled, but if it is not fulfilled, it cannot be recognized as revenue. The income transactions in question are; Road Lighting Tax Revenues, Land and Building Rights Acquisition Tax Revenues, Non-Rock Minerals Tax, Retribution Revenues, Other Legitimate Revenues include sales of official vehicles, late fees, receipt of health insurance), income Central transfer of funds for Special Allocations and Other Legislative income under regional grant agreements. The results of the identification are expected to be the basis of prudence for the management of regional assets transactions in recognizing income transactions in order to avoid future uncertainties which result in the resulting financial statements knowing the element of uncertainty